PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP NIAT KELUAR KARYAWAN DI PT ELEKTRONIK DISTRIBUSI OTOMATISASI TERKEMUKA (eDOT) - Tami Apriliani; Aditya Yudanegara (JIEM : Journal Of International Entrepreneurship And Management, 2026)
This study aims to analyze the conditions of work motivation, work environment, and employee turnover intention, as well as examine the effects of work motivation and work environment on turnover intention at PT Elektronik Distribusi Otomatisasi Terkemuka (eDOT). The company has experienced a high employee turnover rate, reaching 47.01% in 2024 and 42.86% in 2025, exceeding its annual target of 30%. This research employed a descriptive-verificative quantitative approach involving 156 employees. Data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination. The results indicate that all research instruments are valid and reliable. Work motivation has a negative and significant effect on turnover intention (t = ?6.669; p < 0.001), as does the work environment (t = ?5.211; p < 0.001). Simultaneously, both variables significantly influence turnover intention (F = 50.185; p < 0.001) with an R² value of 0.396, indicating that improving work motivation and the work environment can effectively reduce employees' turnover intention..